Case Report: Left bundle branch pacing in an amyloid light-chain cardiac amyloidosis patient with atrioventricular block - Yu, Jiaqi; Kong, Fanyi; Gao, Peng; Chen, Taibo; Liu, Yongtai; Cheng, Zhongwei; Deng, Hua; Lai, Jinzhi; Zhang, Lihua; Fan, Jingbo; Wang, Jiaqi; Qin, Xiaohan; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Amyloid light chain cardiac amyloidosis is a progressive infiltrative disease attributed to the deposition of amyloid fibrils at the cardiac level which can cause serious atrioventricular block requiring pacemaker implantation. Left bundle branch pacing has emerged as an alternative method for delivering physiological pacing to achieve electrical synchrony of the left ventricle. However, left bundle branch pacing in amyloid light chain cardiac amyloidosis patients has not been studied in detail. We present a case of left bundle branch pacing in a patient with amyloid light chain cardiac amyloidosis. Case Summary: A 66-year-old male patient with amyloid light chain cardiac amyloidosis presented with syncope for one month and the Holter monitoring revealed intermittent third-degree atrioventricular block. Left bundle branch pacing was performed successfully. During 1-year follow-up, the left bundle branch capture threshold remained stable without pacemaker-related complications or left ventricle systolic dysfunction, and no syncope reoccurred. Conclusion: Left bundle branch pacing could be applied to amyloid light chain cardiac amyloidosis patients with atrioventricular block with safety and feasibility.